Bioinspired nano-vaccine construction by antigen pre-degradation for boosting cancer personalized immunotherapy. (August 2022) - Zhang, Qiu-Ling; Hong, Sheng; Dong, Xue; Zheng, Di-Wei; Liang, Jun-Long; Bai, Xue-Feng; Wang, Xia-Nan; Han, Zi-Yi; Zhang, Xian-Zheng
Abstract: Cancer vaccines-based cancer immunotherapy has drawn widespread concern. However, insufficient cancer antigens and inefficient antigen presentation lead to low immune response rate, which greatly restrict the practical application of cancer vaccines. Here, inspired by intracellular proteasome-mediated protein degradation pathway, we report an antigen presentation simplification strategy by extracellular degradation of antigen proteins into peptides with proteolytic enzyme for improving the utilization of cancer antigens and arousing restricted cancer immunity. The pre-degraded antigen peptides are first validated to exhibit an increased capacity on antigen-presenting cell (APC) stimulation compared with proteins and still reserve antigen specificity and major histocompatibility complex (MHC) affinity. Furthermore, by coordinating the pre-degraded peptides with calcium phosphate nanoparticles (CaP), a CaP-peptide vaccine (CaP-Pep) is constructed, which is verified to induce an efficient personalized immune response in vivo for multi-model anti-cancer therapy. Notably, this bioinspired strategy based on extracellular enzymatic hydrolysis for vaccine construction is not only applicable for multiple types of cancers, but also shows great potential in expanding immunology fields and translational medicine.